Comparison of immune responses and resistance to brucellosis in mice vaccinated with Brucella abortus 19 or RB51. - Stevens, M G (1995)
Immune responses and resistance to infection with Brucella abortus 2308 (S2308) were measured in mice following vaccination with B. abortus 19 (S19) or the lipopolysaccharide (LPS) O-antigen-deficient mutant, strain RB51 (SRB51). Live bacteria persisted for 8 weeks in spleens of mice vaccinated with 5 x 10(6) or 5 x 10(8) CFU of SRB51, whereas bacteria persisted for 12 weeks in mice vaccinated with 5 x 10(6) CFU of S19. Mice vaccinated with 5 x 10(6) or 5 x 10(8) CFU of SRB51 had increased resistance to infection with S2308 at 12, 16, and 20 weeks after vaccination, but the resistance was lower than that induced by vaccinating mice with 5 x 10(6) CFU of S19. Spleen cells obtained from mice vaccinated with S19 or SRB51 generally exhibited similar proliferative responses to S2308 bacteria or bacterial proteins (106 to 18 kDa) following challenge of mice with S2308 at 12, 16, or 20 weeks after vaccination. Mice vaccinated with S19 had antibody to S2308 bacteria and S2308 smooth LPS at 4, 8, and 12 weeks after vaccination. In contrast, mice vaccinated with either dose of SRB51 did not produce antibody to S2308 smooth LPS. In addition, only mice vaccinated with the highest dose of SRB51 (5 x 10(8) CFU) had antibody responses to S2308 bacteria, although the responses were lower and less persistent than those in mice vaccinated with S19. Collectively, these results indicate that SRB51-vaccinated mice have similar cell-mediated immune responses to S2308 but lower resistance to infection with S2308 compared with S19-vaccinated mice. The lower resistance in SRB51-vaccinated mice probably resulted from a combination of rapid clearance of SRB51 and an absence of antibodies to S2308 LPS.